Emotional difficulties and post-traumatic stress disorder symptoms in children refugees & the role of ICTs: A case study in northern Greece borders - Stathopoulou , Agathi; Liouni , Magdalini; Salapata , Yolanda; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The aim of this study was to investigate the emotional difficulties and post-traumatic stress disorder symptoms within children refugees in northern Greece borders. The present research focuses on the traumatic and emotional difficulties experienced by children refugees, who have been separated from their families during their journey to Europe. This study adopted a research approach with a sample of five children from Syria, of both sexes, aged 11 to 16 years. Each participant was given an Android-based mobile phone with the online forms of the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) and the Achenbach Adolescent Self-Report Questionnaire (YSR 11-18). The completion results showed high levels of post-traumatic stress disorder and intensive emotional problems in the sample of refugees children. In particular, the findings showed a correlation between the level of emotional problems and post-traumatic stress disorder and the type of trauma related to the family traumatic experience.